The institutionalization of the Czech Party System from the point of view of Scott Mainwaring's theory - Hanáček, Vladimír (Civilia, 2012)
The aim of this article is on the basis of the theory of institutionalization of party system of the American political scientist Scott Mainwaring to insight crucial developmental aspects of the Czech Party System and assess throw the findings, whether it can be considered as more or less institutionalized according to four Mainwaring's criteria of institutionalization and describe the factors, which have serious impact to the degree of institutionalization of the Czech Party System.
Keywords: Party System; Institutionalization; Scott Mainwaring; Czech politics